PELUANG BISNIS ONLINE STRAP MASKER DI MASA PANDEMI COVID-19 DI DESA WATULANGKAH, SLEMAN - Putry, Nur Anita Chandra; Ayem, Sri; Prastyatini, Sri Lestari Yuli; Cahya, Agus Dwi (Jurnal Edukasi Pengabdian Masyarakat, 2025)
The Covid-19 pandemic has had a negative impact on the community, some people have lost their jobs in various sectors, and not a few people have experienced difficulties related to the economy. Community service activities in Watulangkah RT 01 RW 36, Ambarketawang, Gamping, Sleman, Yogyakarta aim to increase knowledge related to business opportunities and increase community income by utilizing technology. The method used in this community service which was carried out on January 11, 2022 was mentoring and training related to online business opportunities for mask straps during the Covid-19 pandemic. The results achieved are increased knowledge and development related to online business opportunities. In addition, it provides training in making mask straps and online business. The community can determine where to go that is more advanced and correct and not afraid / worried about every changing condition in this day and age such as pandemics, etc.